IMPLEMENTASI PRODUK PEMBIAYAAN KREDIT USAHA RAKYAT (KUR) MIKRO DALAM MENGEMBANGKAN USAHA MIKRO NASABAH PERBANKAN SYARIAH - Velin Diani; Moh. Rois Abin (Journal of Management Small and Medium Enterprises (SMEs), 2023)
Micro KUR is a financing product that is intended for micro-entrepreneurs. The purpose of this study is to find out the level of public knowledge of KUR micro products, determine the selection of tenors or the period and dine out the accuracy of the spending on business credit financing products. This study focuses on the people of Sobontoro Village Boyolangu District who apply for Micro KUR financing products at Islamic Banks due to being many KUR financing customers and micro businesses in this area such as convection, traders, open stalls, fisheries, and agriculture. This study is qualitative research with a descriptive approach. The data was obtained from observations, interviews, and documentation. The results of this study revealed that the public has knowledge about the KUR financing products and they chose the right tenor so that they can pay installments according to timeliness. The spending on KUR financing products is appropriate for business capital, not for consumptive. Keywords: Micro KUR Financing; Micro Business; Syariah Banking